Biointerface engineering nanoplatforms for cancer-targeted drug delivery - Huaiyu Zhang; Shujun Dong; Zhongmin Li; Xiangru Feng; Weiguo Xu; Catrina Mae S. Tulinao; Yang Jiang; Jianxun Ding (Elsevier, 2020)
Over the past decade, nanoparticle-based therapeutic modalities have become promising strategies in cancer therapy. Selective delivery of anticancer drugs to the lesion sites is critical for elimination of the tumor and an improved prognosis. Innovative design and advanced biointerface engineering have promoted the development of various nanocarriers for optimized drug delivery. Keeping in mind the biological framework of the tumor microenvironment, biomembrane-camouflaged nanoplatforms have been a research focus, reflecting their superiority in cancer targeting. In this review, we summarize the development of various biomimetic cell membrane-camouflaged nanoplatforms for cancer-targeted drug delivery, which are classified according to the membranes from different cells. The challenges and opportunities of the advanced biointerface engineering drug delivery nanosystems in cancer therapy are discussed.